Identification of Mathematics Questions in Student Books for Curriculum 2013 based on Cognitive Dimensions by TIMSS - Sriyanti, A; Pusphita, Viana (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2022)
Abstract:TIMSS (Trends in International Mathematics and Science Study) study shows that Indonesia's mathematical problem-solving ability scores are below the average. This study aims to identify math problems in the 2013 grade VII curriculum students' books for even semesters based on the cognitive dimensions of TIMSS. This research is library research using a qualitative approach. The instrument in this study uses analytical guidelines based on the cognitive dimensions of the 2015 TIMSS, which consists of three domains, namely knowledge (knowing 35%), application (applying 40%), and reasoning (reasoning 25%). The results of the identification of 150 questions in which were identified obtained the level of the proportion of cognitive domains by the proportions tested in the TIMSS. The questions in the book have provided provisions for preparing and empowering students' thinking development to solve mathematical problems.Abstrak:TIMSS (Trends in Internasional Mathematics and Science Study) menunjukkan bahwa kemampuan pemecahan masalah matematika siswa Indonesia masih berada di bawah rata-rata. Penelitian ini bertujuan untuk mengidentifikasi soal matematika dalam buku siswa kurikulum 2013 kelas VII semester genap berdasarkan dimensi kognitif dari TIMSS. Penelitian ini bersifat kepustakaan dengan menggunakan pendekatan kualitatif. Instrumen dalam penelitian ini menggunakan pedoman analisis berdasarkan dimensi kognitif dari TIMSS 2015 yang terdiri atas tiga domain yaitu pengetahuan (knowing 35%), penerapan (applying 40%), dan penalaran (reasoning 25%). Hasil identifikasi dari 150 soal diperoleh tingkat proporsi domain kognitifnya sesuai dengan proporsi yang diuji dalam TIMSS. Soal-soal dalam buku tersebut sudah mampu memberikan bekal dalam mempersiapkan dan memberdayakan tingkat perkembangan berpikir siswa untuk memecahkan masalah matematika.